Thermal recovery process of a backfilled open-pit in permafrost area at the Gulian strip coal mine in Northeast China - GAO Shu-hui; HE Rui-xia; JIN Hui-jun; HUANG Ya-dong; ZHANG Jian-ming; LUO Dong-liang (Journal of Mountain Science, 2017)
Timely and proper backfilling of open-pits in strip coal-mines has been an effective measurement for the recovery of the hydrothermal regimes and ecological environment in permafrost regions. In this study, numerical simulations and statistical regressions were applied for analyzing the recovery processes of the backfill and its major influencing factors for the thermal equilibrium in recently backfilled open pits at the Gulian strip coal-mine in Mo'he, Northeast China. Results show that the thermal recovery time of backfilled areas is positively correlated to the backfill depth (BD) of the soils, the backfilled soil temperature (BST), and the mean annual ground surface temperature (MAGST); meanwhile, climate warming can impact on thermal regimes of the backfill area. The impact of climate warming on ground temperature of the backfill will show up significantly in about 50 years after backfilling (BD at 10.0 and 20.0 m, BST at 20.0°C) under the climate warming scenario (CWS) of 0.025°C·year−1. Grey-relation analyses show that the sensitivity of the backfill recovery time declines in the order of the BD, BST and MAGST. On the basis of the abovementioned studies, the layer-by-layer backfilling in cold seasons is advised for more effective and more rapid recovery of thermal regimes of the backfilled open-pits in cold regions.